Long-term policy impacts of the coronavirus: normalization, adaptation, and acceleration in the post-COVID state - Giliberto Capano (16734990) (2022)
This paper offers an analysis of the theoretical and empirical challenges the coronavirus pandemic poses for theories of policy change. Critical events like coronavirus disease are potentially powerful destabilizers that can trigger discontinuity in policy trajectories and thus are an opportunity for accentuating path shifts. In this paper, we argue that three dynamic pathways of change are possible and must be considered when analysing post-COVID policymaking: normalization, adaptation, and acceleration. These different pathways need to be explored in order to understand the mid- and long-term policy effects of the pandemic. This introduction contextualizes the articles in this special issue, situating them broadly within two broad categories: (a) assessment of how the coronavirus disease pandemic should be understood as a crisis event, and its role in relationship to mechanisms of policy change; and (b) mapping the future contours of the pandemic’s impact on substantive policy areas, including education, health care, public finance, social protection, population ageing, the future of work, and violence against women. Other Information Published in: Policy and Society License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/polsoc/puab018